2020
DOI: 10.31223/x5gp45
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A data assimilation approach to last millennium temperature field reconstruction using a limited high-sensitivity proxy network

Abstract: Paleoclimate field reconstructions using data assimilation commonly employ large proxy networks, which are often composed of records that have a complex range of sensitivities to the target climate field. This can introduce biases into reconstructions or decrease overall skill. Smaller networks of highly-sensitive proxies provide an alternative, but have not been extensively used for assimilation and their strengths and limitations are less well understood. Here, we reconstruct Northern Hemisphere summer tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…(2021), a geographically extensive cooling signature across NWNA is also apparent in gridded spatial reconstructions of warm‐season temperatures derived from a Northern Hemisphere tree‐ring network (Figure 4 showing the King et al. (2021a, 2021b) data set, with anomalies relative to the 1951–1980 CE mean; also seen in Figure S5 of Supporting Information comparison with Anchukaitis et al. (2017)).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…(2021), a geographically extensive cooling signature across NWNA is also apparent in gridded spatial reconstructions of warm‐season temperatures derived from a Northern Hemisphere tree‐ring network (Figure 4 showing the King et al. (2021a, 2021b) data set, with anomalies relative to the 1951–1980 CE mean; also seen in Figure S5 of Supporting Information comparison with Anchukaitis et al. (2017)).…”
Section: Resultsmentioning
confidence: 60%
“… Temperature anomalies across northern North America following the 1809 eruption. These maps show a spatial reconstruction (King et al., 2021a, 2021b) of warm‐season (May–August) temperature anomalies (relative to the 1951–1980 CE mean) across northern North America from 1809 to 1814. The dots in the 1809 panel show the central location of the tree‐ring records in northwestern North America analyzed in this study and shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations